Analysis of Business Competitive Strategies Through The IFE and EFE Matrix of Oyster Mushroom in Pagadungan Village, Karawang - Irfan, Yusuf; Suri, Anita (DPPM Universitas Pelita Bangsa, 2024)
Oyster mushroom is one of the horticultural commodities that has high economic value and is very popular with the community because it is beneficial for health. The author has conducted research on the oyster mushroom business in Pagadungan Village, Tempuran District, during the study in July on July 16, 2023. Using a descriptive method, the data used is qualitative, the research design uses a survey method. The sampling technique used was purposive sampling. The sample is the owner. The process of collecting data using observation, interviews and documentation. Data analysis techniques using SWOT analysis, IFAS and EFAS. The results of the study on the oyster mushroom business in Pagadungan village had an internal strength value of 1.44 while a weakness of 0.44 with an x-axis of 1.58. Meanwhile, the external factor, opportunity, has a score of 1.72 and a threat of 0.78 with a value on the y axis of 2.5, so the strategic position is in quadrant I, namely supporting an aggressive growth strategy (S-O strategy). The resulting S-O strategy is to produce products that exceed production targets to meet market demand, and utilize existing resources to establish partnerships with suppliers.